A pilot randomized controlled trial to examine the impact of a therapy dog intervention on loneliness in adult patients hospitalized in a psychiatric unit - Gee, Nancy R.; Townsend, Lisa; Friedmann, Erika; Barker, Sandra B.; Thakre, Tushar P.; Mueller, Megan K. (Frontiers in Psychiatry, 2025)
Background and objectivesLoneliness has been linked to a number of health threats and is associated with significant morbidity and mortality risks among people with mental illness. Loneliness fully mediates the relationship between societal stigma and depression as well as thoughts of self-injury and is a precursor to suicide attempts and relapse in people with substance misuse disorders.Research design and methodsIndividuals hospitalized for the treatment of mental illness (N = 60) were randomly assigned to one of three conditions: dog + handler intervention (AAI), handler only conversational control (CC), or usual care (UC) for 20 minutes per day for three days. An Analog scale and two versions of the UCLA loneliness scale (UCLA-SF and UCLA-LS) were used to assess loneliness. Linear Mixed Models with random intercepts were applied to compare changes in loneliness between conditions pre/post daily intervention sessions, pre/post 3-day intervention phase (days 2–4), and baseline to post-intervention (days 1–5).ResultsLoneliness decreased significantly more in the AAI group relative to the CC or UC groups in daily pre/post intervention sessions, and over the course of the 3-day intervention for all participants (p <.01). Within those results nuanced male/female sex differences and dog ownership status differences are reported. In stratified analysis, reduction in loneliness for the AAI group occurred from baseline to follow-up, but only among dog owners (p <.01).Discussion and implicationsThese results indicate that AAI was effective for reducing loneliness in people who are hospitalized for the treatment of mental illness. These results support and extend previous research and suggest that AAI has the potential to be effective as an adjunctive treatment for loneliness among people hospitalized for mental illness.Clinical Trial Registrationclinicaltrials.gov identifier, NCT05089201.